Equivalence Problem Solvability in Biparametric Gateway Program Models - A. E. Molchanov (Моделирование и анализ информационных систем)
Algebraic program models with procedures are designed to analyze program semantic properties on their models called program schemes. Procedural liberisation problem and equivalence problem are stated for program models with procedures in which both defining parameters are chosen independently. Program models with procedures built over a given program model without procedures are investigated. Algorithms for both stated tasks are proposed for models where an additional restriction is applied: the intersection emptiness problem is solvable in the program model without procedures. Polynomial estimates for the complexity of the algorithms are shown. Some topics for further investigation are proposed.